Relevansi Prinsip Keseimbangan dalam Konsep Kafaah Perspektif Jasser Audah - Tata Cahwiyadi; Nurnazli; Liky Faizal (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study focuses on analyzing the concept of kafᾱ’ah (compatibility) from the perspective of Maqāṣid al-Sharia as articulated by Jasser Auda, particularly concerning the principle of social balance recognized in Islamic marital law. Kafᾱ’ah, or the compatibility between prospective spouses, is viewed as an essential factor supporting marital harmony and household stability. This research identifies how kafᾱ’ah contributes to a fair and balanced social structure within Muslim societies and reduces potential incompatibilities that may lead to marital instability. Using a sociological approach and Jasser Auda’s systems theory, this study elucidates the relationship between kafᾱ’ah and the objectives of Sharia, or Maqāṣid al-Sharia. Through content analysis and qualitative descriptive methods, the research examines relevant primary and secondary sources, including both classical and contemporary texts. Findings show that kafᾱ’ah not only fosters marital harmony but also functions as a social balancing mechanism that strengthens stability in Muslim communities. These findings highlight the relevance of Maqāṣid al-Sharia, particularly Jasser Auda’s insights into the principle of balance in kafᾱ’ah , as a foundation for establishing justice in social relationships and addressing inequality issues in marriage. This study aims to contribute to academic discussions and provide practical benefits for the application of kafᾱ’ah in family law policies within contemporary Muslim societies.